Disappearing cryptography : information hiding : steganography & watermarking - Wayner, Peter, 1964- (Morgan Kaufmann Publishers, 2002)
Disappearing Cryptography, Second Edition describes how to take words, sounds, or images and hide them in digital data so they look like other words, sounds, or images. When used properly, this powerful technique makes it almost impossible to trace the author and the recipient of a message. Conversations can be submerged in the flow of information through the Internet so that no one can know if a conversation exists at all. This full revision of the best-selling first edition describes a number of different techniques to hide information. These include encryption, making data inc.